Dampak E-Commerce Terhadap Pertumbuhan Jiwa Entrepreneurship Mahasiswa - Mardhiyah Hayati (Nizham Jurnal Studi Keislaman, 2017)
In the era of globalization, the exsisting of Internet has viewed a global information network that completely transparent, it was directly or indirectly affect and create challenges to find the way of arranging a transaction in the economics side, the development of technology has met the method of transactions known as e-commerce. Islam has set up a mechanism in the property development, and one of the efforts for arrange the wealth development is through business activities. Young age is not an obstacle to starting a business, even many people who success in the field of business at a young age. Based on the background above, the formulation of the problem in this study: How big is the impact of e-commerce on Soul Entrepreneurship Growth Student Faculty of Economics and Islamic Business, UIN Raden Intan Lampung ?. Research Objectives to analyze how big is the impact of e-commerce on the Growth of Enterpreneurship Student Life of Faculty of Economics and Islamic Business, UIN Raden Intan Lampung. The method cunducted in this research is using survey research design with quantitative research methods, the sample in this study as many as 19 people with simple random sampling method, data collecting techniques that used was through questionnaires, data analysis techniques is using a simple regression by SPSS program ver. 16. The results showed: There are positive and significant impact between e-commerce with the growth of soul students entrepreneurship.